Step
*
2
1
1
of Lemma
Cn-comb_wf
.....subterm..... T:t
1:n
1. T : Type
2. n : ℤ
3. 0 < n
4. ∀m:ℕ. ∀A:ℕm ⟶ Type.
     (n - 1 < m
     
⇒ (primrec(n - 1;λf.f;λi,F,f,x. (F (C-comb() f x))) ∈ funtype(m;A;T) ⟶ funtype(m;λk.if k <z n - 1 then A (k + 1)
                                                                                   if (k =z n - 1) then A 0
                                                                                   else A k
                                                                                   fi T)))
5. m : ℕ
6. A : ℕm ⟶ Type
7. n < m
8. 1 ≤ n
9. f : funtype(m;A;T)
10. x : A 1
⊢ primrec(n - 1;λf.f;λi,F,f,x. (F (C-comb() f x))) (C-comb() f x) ∈ funtype(m - 1;λk.if k <z n - 1 then A (k + 2)
                                                                             if (k =z n - 1) then A 0
                                                                             else A (k + 1)
                                                                             fi T)
BY
{ ((InstLemma `C-comb_wf_funtype` [⌜T⌝;⌜m⌝;⌜A⌝]⋅ THENA Auto) THEN (GenConclTerm ⌜C-comb() f⌝⋅ THENA Auto)) }
1
1. T : Type
2. n : ℤ
3. 0 < n
4. ∀m:ℕ. ∀A:ℕm ⟶ Type.
     (n - 1 < m
     
⇒ (primrec(n - 1;λf.f;λi,F,f,x. (F (C-comb() f x))) ∈ funtype(m;A;T) ⟶ funtype(m;λk.if k <z n - 1 then A (k + 1)
                                                                                   if (k =z n - 1) then A 0
                                                                                   else A k
                                                                                   fi T)))
5. m : ℕ
6. A : ℕm ⟶ Type
7. n < m
8. 1 ≤ n
9. f : funtype(m;A;T)
10. x : A 1
11. C-comb() ∈ funtype(m;A;T) ⟶ funtype(m;λk.if (k =z 0) then A 1
                                              if (k =z 1) then A 0
                                              else A k
                                              fi T)
12. v : funtype(m;λk.if (k =z 0) then A 1
                     if (k =z 1) then A 0
                     else A k
                     fi T)
13. (C-comb() f) = v ∈ funtype(m;λk.if (k =z 0) then A 1 if (k =z 1) then A 0 else A k fi T)
⊢ primrec(n - 1;λf.f;λi,F,f,x. (F (C-comb() f x))) (v x) ∈ funtype(m - 1;λk.if k <z n - 1 then A (k + 2)
                                                                    if (k =z n - 1) then A 0
                                                                    else A (k + 1)
                                                                    fi T)
Latex:
Latex:
.....subterm.....  T:t
1:n
1.  T  :  Type
2.  n  :  \mBbbZ{}
3.  0  <  n
4.  \mforall{}m:\mBbbN{}.  \mforall{}A:\mBbbN{}m  {}\mrightarrow{}  Type.
          (n  -  1  <  m
          {}\mRightarrow{}  (primrec(n  -  1;\mlambda{}f.f;\mlambda{}i,F,f,x.  (F  (C-comb()  f  x)))  \mmember{}  funtype(m;A;T)  {}\mrightarrow{}  funtype(m;\mlambda{}k.if  k  <z  n\000C  -  1
                                                                                                                                                                          then  A  (k  +  1)
                                                                                                                                                                      if  (k  =\msubz{}  n  -  1)
                                                                                                                                                                          then  A  0
                                                                                                                                                                      else  A  k
                                                                                                                                                                      fi  ;T)))
5.  m  :  \mBbbN{}
6.  A  :  \mBbbN{}m  {}\mrightarrow{}  Type
7.  n  <  m
8.  1  \mleq{}  n
9.  f  :  funtype(m;A;T)
10.  x  :  A  1
\mvdash{}  primrec(n  -  1;\mlambda{}f.f;\mlambda{}i,F,f,x.  (F  (C-comb()  f  x)))  (C-comb()  f  x)  \mmember{}  funtype(m  -  1;\mlambda{}k.if  k  <z  n  -  1
                                                                                                                                                              then  A  (k  +  2)
                                                                                                                                                          if  (k  =\msubz{}  n  -  1)
                                                                                                                                                              then  A  0
                                                                                                                                                          else  A  (k  +  1)
                                                                                                                                                          fi  ;T)
By
Latex:
((InstLemma  `C-comb\_wf\_funtype`  [\mkleeneopen{}T\mkleeneclose{};\mkleeneopen{}m\mkleeneclose{};\mkleeneopen{}A\mkleeneclose{}]\mcdot{}  THENA  Auto)
  THEN  (GenConclTerm  \mkleeneopen{}C-comb()  f\mkleeneclose{}\mcdot{}  THENA  Auto)
  )
Home
Index